Fatores de risco maternos presentes no nascimento de prematuros: uma revisão de literatura - BOÁS, Mariana Reis (2019)
This research had as its object of study the knowledge produced about the main risk factors that lead to the birth of premature newborns. Each year about 15 million babies are born premature in the world.More than 1 million of them die within days of birth. In Brazil there are 279,3 million premature births a year, occupying the 10th position in absolute numbers of premature births.The study aimed to discourse, through the review of literature, the main risk factors for preterm birth; Describe the role of the nurse in health promotion and prevention of these risk factors. The method used was a literature review of the narrative type. To obtain the data, we used the bibliographical survey conducted in major bibliographic databases and electronic journals portals: Bireme, SciELO, VHL, Lilacs, involving articles, monographs, dissertations and theses that address the major factors that lead to the birth of premature infants in the period 2001-2013.After the search for material on prematurity we showed that the production of scientific knowledge in the case of the main risk factors for prematurity, mainly addressed factors such as socioeconomic status, maternal education, ethnicity / race, maternal age, preeclampsia, urinary tract infection , vulvovaginal infection, iron deficiency anemia, twin pregnancy, gestational diabetes, alcohol abuse and drug abuse, malnutrition and underweight mothers.The study was of fundamental importance to improve our knowledge about the main risk factors for prematurity, since the incidence of preterm birth remains high in every year, mainly in developing countries like Brazil.